MENINGKATKAN MINAT BELAJAR MATEMATIKA MELALUI PERMAINAN TEKA-TEKI - Wicka Yunita Dwi Utami (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
This research aims to increase the early age children’s interest in learning math through puzzle game. This study was conducted in grade 1, SDN Kaloran Kidul in May to June 2012. The method used was action research conducted through two cycles each of which consisted of planning, action, observation, and reflection. The subjects were ten children of with interest problems in learning math. The data were collected using tests and non-test and analyzed with the percentage technique agreed by the collaborator and researcher. The results show that the puzzle game can be used to increase the students’ interest in learning math. The implications of these results among others is the puzzle game can be used as an alternative method to improve the children’s interest in learning math. The interest increase can be seen from the children’s sense of love or interest, concern, desire, seriousness and satisfaction in learning mathematics.